Variable Exponent Function Spaces related to a Sublinear Expectation - Bochi Xu (Abstract and Applied Analysis)
In this paper, variable exponent function spaces Lp·, Lbp·, and Lcp· are introduced in the framework of sublinear expectation, and some basic and important properties of these spaces are given. A version of Kolmogorov’s criterion on variable exponent function spaces is proved for continuous modification of stochastic processes.